2020
DOI: 10.1088/1748-9326/ab6ae3
|View full text |Cite
|
Sign up to set email alerts
|

The end of gunpoint conservation: forest disturbance after the Colombian peace agreement

Abstract: In November 2016, after 52 years of armed conflict, the Colombian government and the primary rebel group, the FARC (Fuerzas Armadas Revolucionarias de Colombia) reached a peace agreement. The agreement incorporated three changes to institutions governing forest land occupation and use: (a) the demobilization of FARC from forested places, (2) the future distribution of legal land titles and new road construction into forests, and (3) the eradication of illicit crops. However, we document unprecedented rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 55 publications
(41 reference statements)
5
40
1
7
Order By: Relevance
“…These groups are re-activating old tracks used during the past conflict and opening new ones, to create a political-military transportation network. This territorial-control strategy allows consolidating a social basis for these armed groups, economic inputs for rearmament, and a www.nature.com/scientificreports www.nature.com/scientificreports/ population exploiting this 'territorial security' , which also represents a source of recruitment for the guerrillas 37 . A new long-term cycle of violence is potentially incubating in these regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These groups are re-activating old tracks used during the past conflict and opening new ones, to create a political-military transportation network. This territorial-control strategy allows consolidating a social basis for these armed groups, economic inputs for rearmament, and a www.nature.com/scientificreports www.nature.com/scientificreports/ population exploiting this 'territorial security' , which also represents a source of recruitment for the guerrillas 37 . A new long-term cycle of violence is potentially incubating in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Communities living in regions structurally characterized by lack of infrastructural development and established stable markets, often rely on forest clearing to claim land for subsistence agriculture or more profitable illicit activities. In Colombia, for example, rural settlers and small farmers, were found to be selling deforested land, in some cases opportunistically, in others under duress, to larger, well-organized agricultural producers, who in turn expect the government to adopt land tenure policies favorable to their interests 37 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recently study by Murillo et al (2020) found that during the post-peace agreement period (2017-2018), in the LHFI hotspot of Andean-Amazon foothills (see hotspot IV in Figure 4) forest disturbance increased by 50% over the estimate of 2013-2016 (Hoffmann et al, 2018).…”
Section: Human Impact and Threatened Ecosystemsmentioning
confidence: 93%
“…On the one hand, studies showed that conflict zones have experienced reforestation and increased protection of biodiversity [9,10], for example, as a side-effect of land abandonment [11]. On the other hand, studies also found that peace agreements may lead to negative outcomes for the environment as they incentivize economic development, as evident in Colombia where deforestation has increased since the ratification of the peace agreement between the government and the Fuerzas Armadas Revolucionarias de Colombia [12,13]. Furthermore, armed conflicts can affect non-adjacent areas through the movement of refugees [14], indicating, among other things, a telecoupling effect [15].…”
Section: Introductionmentioning
confidence: 99%